The Divine Economy: How Religions Compete for Wealth, Power, and People - Becker, Sascha O. (Journal of Economic Literature, 2024)
Sascha O. Becker of Monash University and University of Warwick reviews “The Divine Economy: How Religions Compete for Wealth, Power, and People” by Paul Seabright. The Econlit abstract of this book begins: “Presents a platform model of religious movements, discussing how the competition for members and resources between such movements shapes what is possible for them and their political backers.”